Legal policy justification for the crime of non-covered use of payment cards - Vuković Igor; Radović Mirjana (Anali Pravnog Fakulteta u Beogradu)
In this paper the authors discuss the legal policy reasons for the crime of non-covered use of payments cards (Criminal Code, Art. 228(1)). In the first part of the paper the ratio legis of this crime is explained. It is concluded that the non-covered use of payment cards deserves to be criminally sanctioned only when, based of the card's use, the card issuer becomes personally liable for payment to the third party not privy to the contract between the issuer and the card-holder. Conversely, criminal proscribing is not justified when debit cards are used at the point-of-sale or the ATM of another bank, since here the issuer authorizes the payment transaction and thereby participates in assuming his own obligation to pay to the third party. The second part of the paper contains critical analysis of the proscribed non-covered use of payment cards in the Serbian Criminal Code. In this respect the authors show the lack of clarity and certain discrepancies with the explained ratio legis of such a crime. Based on the comprehensive analysis of the issues regarding the justification of criminal proscribing in this field, in the last part of the paper the authors suggest possible solutions de lege ferenda.